Autism Spectrum Disorders: From Etiology and Manifestations to Dental Treatment and Prevention - Ramya R; Eswari R; Aruna Sharma (Disease and Health: Research Developments Vol. 3, 2025)
Autism spectrum disorder (ASD) is a neurodevelopmental disorder characterized by impairments in social, communication and functional skills with restricted or repetitive behavioral stereotypes. The prevalence of ASD is rising and has been estimated to be one in every 100 children, with a male predilection of 5:1. Although there are no known autism-specific oral manifestations, oral health problems could arise due to autism-related behaviors. Dental caries and periodontal disease are the most prevalent oral health issues experienced by children with ASD. The incidence of dental caries among ASD children varied from 60.6% to 67.3%, whereas periodontal disease prevalence ranged from 59.8% to 69.4%. Due to a lack of cooperation with clinical oral examinations, assessing the oral health requirements of children with ASD is challenging. Visual pedagogy, video modelling, the Picture Exchange Communication System, and yoga as adjunct treatment have all been utilised to encourage positive behaviours and communication. Pediatric dentists must understand the oral health condition of children with autism. Due to the compromised communication with the caregivers and their oral sensitivities, dental management of children with ASD is challenging. Therefore, this monograph gives insight into managing children with ASD and behavior guidance.